Relevansi dan Tantangan Implementasi Program Bantuan Sosial dalam Mendorong Pemulihan Ekonomi Lokal di Kota Tanjungpinang - Siahaan, Sonia Trifosa; Siregar, Agatha Cristy; Aryanisah, Bintang; Pangestoeti, W (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
Poverty is one of the main problems faced by developing countries, including the city of Tanjungpinang, Indonesia. Various challenges still have to be faced in efforts to improve the welfare of the population, especially among low-income communities. This research aims to evaluate the effectiveness of the implementation of social assistance programs in reducing poverty levels in Indonesia. The high poverty rate in various regions has encouraged the government to launch various social assistance programs as a strategic step to ease the economic burden on poor and vulnerable communities. Through this program, it is hoped that the quality of life of the beneficiary community groups can gradually improve. However, in the process of implementing social assistance programs in the field, various obstacles are still encountered, one of which is the problem of inaccurate targeting, where assistance is not fully received by people who really need it, so that the effectiveness of this program is still questionable and requires improvement in various aspects of its implementation. To overcome the problems of poverty and inequality, the government launched the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), Direct Cash Assistance (BLT). This research aims to determine the influence on the implementation of these programs which can be viewed from various aspects, including social, economic, legal, governance and environmental aspects